THE FORMATION AND DEVELOPMENT OF PUBLIC DIPLOMACY IN UZBEKISTAN - Bobomurod Tukhtasinov (Modern American Journals, 2025)
This article examines the essence of public diplomacy, its formation in Uzbekistan, and the process of finding a historical solution. It also examines the importance of public diplomacy in interethnic relations and socio-economic ties between countries.
Keywords: People's diplomacy, Central Asia, geographical space, Sogd-Bactria, peace treaties, diplomatic dialogue, Tashkent spirit.